High compressed hydrogen production via direct electrolysis of liquid ammonia. (7th September 2016) - Goshome, Kiyotaka; Yamada, Takahiro; Miyaoka, Hiroki; Ichikawa, Takayuki; Kojima, Yoshitsugu
Abstract: In this study, the direct electrolysis of liquid ammonia (NH3 ) by using ammonium chloride (NH4 Cl) as an electrolyte to supply ammonium cation ( NH 4 + ) is performed. As a result, it is confirmed that a certain electric current is observed while voltage below 2.0 V is applied to the electrodes, which indicates that NH4 Cl can work as an electrolyte for the electrolysis of liquid ammonia. Furthermore, generation of high compressed hydrogen by NH3 electrolysis is successfully demonstrated, where the inner pressure reaches 20 MPa. However, it is confirmed that the electrode corrosion on the anode occur during the electrolysis. Then, the corrosion mechanism of the anode electrode composed of stainless or platinum are investigated by gas chromatography for the generated gas, and powder x-ray diffraction measurement for the electrolyte after the electrolysis. Finally, it is concluded that a metal ( M ) of an anode electrode is ionized in the ammonia solution to form metal chloride ( M Cl x ) instead of the primary oxidation reaction for the electrolysis of ammonia. Highlights: Direct electrolysis of liquid NH3 with NH4 Cl as an electrolyte is performed. NH4 Cl can work as an electrolyte for NH3 electrolysis. High compressed hydrogen production of 20 MPa is successfully demonstrated. Electrode corrosion on anode should be taken into the consideration.